Rancang Bangun Smart RCBO Berbasis Webserver - Tomi Antonius; Marzuarman Marzuarman; Stephan Stephan; Syaiful Amri; Eva Navasari (Universitas Pahlawan Tuanku Tambusai, 2026)
The development of the Internet of Things (IoT) has encouraged the implementation of intelligent electrical protection systems capable of real-time monitoring. This research aims to analyze and design a Webserver-Based Smart RCBO that can detect overcurrent and leakage current while providing real-time monitoring through a web interface. The system employs a NodeMCU ESP8266 as the main controller and webserver, a ZMCT103C sensor for load current measurement, a Zero Sequence Current Transformer (ZSCT) for leakage current detection, and a relay to disconnect the electrical circuit during fault conditions. Sensor data are displayed on a 16×2 LCD and transmitted to the webserver via a Wi-Fi network. Experimental results indicate that the system is capable of monitoring load current accurately and automatically disconnecting the circuit when the leakage current reaches 30 mA, with a response time ranging from 20 ms to 30 ms. Furthermore, the webserver successfully displays load current, leakage current, RCBO status, and system conditions in real time through a web browser. Therefore, the proposed Webserver-Based Smart RCBO improves electrical safety, reliability, and monitoring efficiency compared with conventional RCBO systems.